Hinglish as a New Linguistic Trend: A Case Study of Bollywood Movies - Arvind Malhotra (Journal of Linguistics and Communication Studies, 2025)
Hinglish, the hybrid blend of Hindi and English, has emerged as a dominant linguistic trend in contemporary Indian society, particularly in Bollywood cinema. This study explores the rise of Hinglish in Bollywood, analyzing its linguistic features, cultural significance, and impact on communication. The integration of Hinglish in Bollywood dialogues reflects broader socio-cultural shifts driven by globalization, changing audience demographics, and identity representation. Through an examination of code-switching structures, lexical borrowing, and character dialogues, this research highlights how Hinglish functions as a marker of modernity and urban sophistication. Additionally, the study discusses the influence of Hinglish on spoken language in India, its role in shaping perceptions of Hindi and English, and the ongoing debates surrounding its use in mainstream media. Finally, this research considers the future trajectory of Hinglish in Bollywood and its potential influence on other multilingual film industries. As Bollywood continues to evolve, Hinglish is expected to maintain its prominence, bridging linguistic divides and reinforcing its status as an integral part of India’s linguistic and cultural identity.